Características e medidas de controle nas duas primeiras ondas epidemicas de Sars-Cov-2 no município de Itapajé, Ceará, 2020 e 2021 - Santos, Jaliana Holanda Nascimento (2023)
The COVID-19 pandemic has been severe in all regions of Brazil. This study aimed to describe the Sars-Cov-2 epidemic and respective control measures in the municipality of Itapajé, Ceará, from April 2, 2020 to December 31, 2021.The study used data from the e-SUS Notifica and SIVEP-Gripe notification systems, epidemiological investigation reports, health surveillance reports, the Municipal Plan for Coping with the COVID-19 pandemic, and municipal decrees. The first case and the control measures were described in narrative form. For spatial analysis, the point distribution of cases and deaths was identified on the Itapajé city map, and the Kernel estimator function was applied. Descriptive analysis was performed using simple and relative frequencies. To identify factors associated with death, relative risks (RR) and 95% CI were calculated and the Chi-square test was applied. Multivariate analysis using Poisson regression was performed to identify factors independently associated with death. There were a total of 3,020 COVID-19 cases; 135 (4.5%) died. Cumulative incidence and mortality rates were 5,650.3 cases and 252.6 deaths per 100,000 inhabitants, respectively. The index case of Sars-Cov-2 was diagnosed in March 2020. The first peak of cases and deaths occurred in May 2020. The second wave of infection peaked in May 2021, with the highest number of deaths in March 2021. In spatial analysis, the highest density of cases and deaths occurred in the urban area. The city government issued 69 decrees on restriction measures, surveillance and maintaining social isolation to deal with the spread of SarsCov-2. The highest proportion of confirmed COVID-19 cases was in the age group 21-50 years (62.2%), females (53.9%), brown race/color (76.8%), and in residents in the urban area of the municipality (83.1%). The highest number of deaths from COVID-19 occurred in the age group o >70 years (43.7%), males (57.8%), brown race/color (87.4%) and residents in the urban area (81.5%). The most frequent signs and symptoms among COVID-19 cases were cough (70.3%), fever (69.2%), sore throat (55.7%) and headache (43%) and among deaths were shortness of breath/dyspnea (92.4%), O2 saturation < 95% (75.6%), cough (74.8%) and fever (67.2%). The most frequent chronic diseases among COVID-19 cases and deaths were chronic heart disease (8.7%/45.2%) and diabetes (4.2%/32.6%). The factors associated with the highest risk of COVID-19 deaths were breathlessness (RR=8.68; 95%CI 4.14 - 18.21), O2 saturation < 95% (RR=7.44; 95%CI 4.57 - 12.12), immunosuppression (RR=2.79; 95%CI 1.07 - 7.29), obesity (RR=1.85; 95%CI 1.25 - 2.73), age group (RR=1.63; 95%CI 1.33 - 1.99) and diabetes (RR=1.35; 95%CI 1.00 - 1.82). Sore throat (RR= 0.63; 95%CI 0.40 - 0.99) was associated with lower risk of death. The spread of the Sars-Cov-2 pandemic in Itapajé mirrored the behavior previously observed in large metropolitan regions, from central neighborhoods to the periphery. The findings of this study are relevant for understanding future pandemics in small municipalities.